Social Context and Sociolinguistic Factors in Second Language Acquisition (SLA): Perceptions of Tertiary Students in Bangladesh - Sharmin Rahman Bipasha; MD NAHIDUL ISLAM (JL3T (Journal of Linguistics, Literature and Language Teaching), 2025)
The research examines how Bangladeshi tertiary students perceive social context and sociolinguistic factors that influence their learning of English. Understanding the influence of social contexts and sociolinguistic elements on English acquisition is essential to create effective educational methods because English language proficiency matters in Bangladesh's current globalization process. The study addresses three essential inquiries regarding social factors that influence target language acquisition and their variation between Bangla and English medium education environments, as well as their influence on final language performance results. Through quantitative research methodology, data were collected from 40 tertiary-level students (equally distributed between Bangla and English medium backgrounds) from three universities using a 15-question survey instrument. The research data demonstrates substantial differences between Bengali and English schools regarding how students learn language. Students from English-medium institutions receive early home-based exposure to English which along with family language usage and continuous motivational support leads to better English skill development while Bangla-medium students encounter English mainly in educational institutions (75%) where they study English as a subject (80%) yet they receive less institutional support for extracurricular English learning. Socioeconomic status proved essential for understanding success in language learning since participants pointed to restricted contact opportunities and ill-prepared teachers, together with limited resources, as essential challenges that prevented underprivileged students from mastering English language skills. Cultural beliefs, along with linguistic nationalism, function as additional obstacles for students to practice English. This scholarly work provides crucial information to second language acquisition theory because it shows how the educational medium, together with socioeconomic background and cultural environment, and motivational elements, develop separate paths for language acquisition. Research data should guide the creation of inclusive language teaching practices and policies that accommodate Bangladesh's varied sociolinguistic diversity.